2010
DOI: 10.1007/s11606-010-1418-6
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Pain Reduction Through Affective Self-awareness in Fibromyalgia: A Randomized Controlled Trial

Abstract: The affective self-awareness intervention improved pain, tenderness, and self-reported physical function for at least 6 months in women with fibromyalgia compared to wait-list control. This study suggests the value of interventions targeting emotional processes in fibromyalgia, although further studies should evaluate the efficacy of this intervention relative to active controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 49 publications
3
73
0
5
Order By: Relevance
“…This version of EAET was modified from previous trials [10,23,30,41] and presented FM as an amplification of CNS pain and sensory processes due to stress or conflict that is followed by emotional avoidance. Becoming aware of and then experiencing and expressing more adaptive emotions, which is then ideally followed by more direct and honest interpersonal interactions, reduces CNS amplification and improves symptoms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This version of EAET was modified from previous trials [10,23,30,41] and presented FM as an amplification of CNS pain and sensory processes due to stress or conflict that is followed by emotional avoidance. Becoming aware of and then experiencing and expressing more adaptive emotions, which is then ideally followed by more direct and honest interpersonal interactions, reduces CNS amplification and improves symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…One small trial found that psychodynamic therapy led to some improvement, but not more than a “high-standard” intervention involving health behavior advice and medication [49]. Another small trial of a group intervention found that emotional awareness and written expression techniques led to substantial pain reduction, compared to wait-list controls [30]. …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, alternative explanations are more convincing, as it has been shown that individuals with fibromyalgia are more likely than controls to have deficits in emotional awareness, and difficulty in distinguishing positive from negative emotions. 30,31 Alternatively, although concordance rates between self and clinician ratings of depression are usually acceptable, significantly discordant ratings have been documented in a substantial number of patients, leading researchers to explore the potential role of other factors in determining the observed discrepancies between self and observer ratings of depression. Personality traits such as higher levels of neuroticism, low extraversion and low agreeableness, younger age, and the nonendogenous subtype of depression were associated with greater endorsement of self-reported depressive symptoms relative to observer ratings.…”
Section: Discussionmentioning
confidence: 99%
“…A distinction is made between primary emotional states (essentially biologically determined drives, motives and impulses), which are adaptive (from an evolutionary point of view), and secondary emotional states (such depression, anxiety and fear), which develop as a consequence of failure to recognize and deal effectively with the primary emotional states, and are essentially maladaptive [35]. In this model emotional processes are seen as essential mediators of the response to pain, and chronic pain is effectively the consequence of emotional dysregulation, solutions for which might include training in mindfulness [36] or emotional disclosure [37,38]. Although these approaches appear promising, further research is needed into their influence on clinical outcome [18].…”
Section: Management Perspective Main Emotional Process-pain Modelmentioning
confidence: 99%